Bariery i szanse rozwoju rolnictwa w Małopolsce po integracji Polski z Unią Europejską - Żmija, Janusz (Barriers and Chances of Agriculture Development in Małopolska after the Integration of Poland with the European Union, 2005)
Fragmented agrarian structure, high amount of labour and low of capital in rural areas influence economic efficiency of economy in agriculture. This causes necessity of development of laborious production directions.Among other barriers of agriculture development are: weak infrastructure, limited capital, lack of non-agricultural jobs, low level of skills and education of rural population and farmers.Modernisation of agriculture and multifunctional rural development are the chances of rural areas.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 2, s. 473-478